The Role of Marketing Public Relations Strategy in Dealing with The Impact of PPKM - Okta Annisa Kusumawardhani; Cindi Purnama Sari; Morelynte Dovena Remeng; Dyva Claretta; Dian Hutami Rahmawati (2022)
International Cultural Center (ICC) Pandaan is one of the resorts and tourist attractions located in Pandaan, East Java. As a resort and tourist attraction, ICC Pandaan has goals to be achieved and the value of benefits provided to its visitors. However, with the Covid-19 pandemic, ICC Pandaan experienced a decrease in the number of visitors, so ICC implemented a strategy to survive during this pandemic. This research is a qualitative descriptive study with data collection techniques conducted through interviews and observations. The result of this research is that ICC Pandaan applies the Three Ways Strategy concept which is carried out effectively by seeking to give messages to the audience by starting to dive into the digital realm, where there has been a rapid increase during the pandemic.